1997
DOI: 10.1002/jor.1100150509
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen tension during cartilage formation by periosteum

Abstract: Tissue engineering makes regeneration of cartilage possible but requires optimization of culture conditions. The effects of oxygen tension on cartilage metabolism are controversial in the literature, and we could find no information detailing the optimal oxygen concentration for growing new cartilage (neochondrogenesis). Periosteal cells and tissues can be used to grow cartilage in vivo and in vitro. In this study, using a standard periosteal organ culture model, we found that cartilage formation by periosteal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 40 publications
3
42
0
4
Order By: Relevance
“…Oxygen tensions of 78-180 mmHg increased GAG synthesis by 2-fold in explants of steer articular cartilage as compared to physiological p O 2 (45 mmHg) (Ysart and Mason, 1994). Similarly, oxygen tensions of 91-114 mmHg enhanced cartilage tissue formation and increased the amount of collagen type II in rabbit periosteal explants cultured in agarose suspension, as compared to p O 2 of 8-38 mmHg which inhibited ECM formation (O'Driscoll et al, 1997). For monolayers of bovine growth plate chondrocytes, highest rates of cell growth and GAG synthesis were observed at p O 2 of 160 mmHg; GAG production rate decreased while the rate of proteoglycan aggregation increased at p O 2 of 22.8 mmHg (Clark et al, 1991).…”
Section: Discussionmentioning
confidence: 73%
“…Oxygen tensions of 78-180 mmHg increased GAG synthesis by 2-fold in explants of steer articular cartilage as compared to physiological p O 2 (45 mmHg) (Ysart and Mason, 1994). Similarly, oxygen tensions of 91-114 mmHg enhanced cartilage tissue formation and increased the amount of collagen type II in rabbit periosteal explants cultured in agarose suspension, as compared to p O 2 of 8-38 mmHg which inhibited ECM formation (O'Driscoll et al, 1997). For monolayers of bovine growth plate chondrocytes, highest rates of cell growth and GAG synthesis were observed at p O 2 of 160 mmHg; GAG production rate decreased while the rate of proteoglycan aggregation increased at p O 2 of 22.8 mmHg (Clark et al, 1991).…”
Section: Discussionmentioning
confidence: 73%
“…The potentiating effect of TGF-P1 on periosteal chondrogenesis, when administered in the presence of fetal bovine serum, is well established [15,30,35,36,42,56,57]. Yaeger et al in developing serum-free media for culturing articular chondrocytes in suspension, found that neither TGF-Pl nor IGF-1 on their own could support the expression of the chondrocyte phenotype, however, the combination of these two growth factors did support the chondrocyte phenotype [69].…”
Section: Discussionmentioning
confidence: 99%
“…Periosteum transplanted into a joint has the potential to repair articular defects with hyaline-like cartilage [32,37,38,42,. This same chondrogenic potential can be demonstrated in vitro [15,30,35,36,42,56,57]. However, the standard organ culture model to date involving whole explants of periosteum has required the addition of fetal bovine serum to the media.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other groups studying cartilage repair have recently demonstrated the ability to transfer and express genes in chondrocytes in vivo in cartilage defect models 25,26 while another study has used nongene-modified periosteal cells in cartilage repair models. 27 In an attempt to develop a gene therapy approach for bone and cartilage repair by delivering a clinically relevant gene, we have demonstrated that retroviral vectormediated delivery of the hBMP-7 gene can be used to transduce primary periosteal cells in vitro. However, our results demonstrate the importance of preventing overexpression of hBMP-7 in target cells due to its apparent toxicity.…”
Section: Discussionmentioning
confidence: 99%